Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$\langle u + v, w \rangle = \langle u, w \rangle + \langle v, w \rangle$ ; $u = (3, -2), v = (4, 5), w = (-1, 6)$

$\langle u, v \rangle = 4u_1v_1 + 5u_2v_2 $

When I tried to do this I got: $\langle u + v, w \rangle = \langle(48, -50), (-1, 6)\rangle = -348$ (probably the wrong answer)

Looking at it, it appears that:

$\langle u, v \rangle = v_1u_1v_1 + v_2u_2v_2$

but I don't know how to deal with the weighted inner product.

share|cite|improve this question
up vote 0 down vote accepted

I got:
$$\langle u + v, w \rangle = \langle (3+4,-2+5),(-1,6)\rangle$$ $$=\langle (7,3),(-1,6)\rangle$$ $$=4( (7)(-1)) + 5((3)(6)) = -28+90=62$$

share|cite|improve this answer
So once you get it down to ⟨(7,3),(−1,6)⟩ you treat it like the ⟨u,v⟩? – user8640 Mar 24 '11 at 1:25
Hey, I'm not an expert, but the weighting can only apply when you do the actual inner product. And <u,w> + <v,w> should get the same result. – Carl Brannen Mar 24 '11 at 1:31

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.